Collective Efficacy and Major Depression in Urban Neighborhoods - Ahern, Jennifer (Oxford University Press, 2011)
Depression contributes substantially to the global burden of disease and disability. Population-level factors that shape depression may be efficient targets for intervention to decrease the depression burden. The authors aimed to identify the relation between neighborhood collective efficacy and major depression. Analyses were conducted on data from the New York Social Environment Study (n = 4,000), a representative study of residents of New York, New York, conducted in 2005. Neighborhood collective efficacy was measured as the average neighborhood response on a well-established scale. Major depression was assessed with the Patient Health Questionnaire. A marginal modeling approach was applied to present results on the additive scale relevant to public health and intervention. Analyses were adjusted for demographic and socioeconomic characteristics, recent life events that could contribute to both depression and change in residence, and individual perception of collective efficacy. Collective efficacy was related to major depression among older adults; marginal models estimated a 6.2% (95% confidence interval: 0.1, 17.5) lower prevalence of depression if all older adults (65 years and older) had lived in high versus low collective efficacy neighborhoods. Similar results were suggested among younger adults; however, the confidence interval crossed the null. These and other study findings suggest that community-randomized trials targeting collective efficacy merit consideration.